The Power of Hedonic Motivation and Discounts through Releasing Impulse Buying in Indonesia: Kekuatan Motivasi Hedonis dan Diskon melalui Melepaskan Impulse Buying di Indonesia - Widyastuti, Nur Azmi; Hariasih, Misti (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the effects of hedonic shopping motivation, price discounts, and shopping lifestyle on impulse buying at TikTok Shops among consumers in Sidoarjo. Using a quantitative explanatory approach, data were collected from 160 respondents through online questionnaires and analyzed with SPSS 22. The results reveal that all three factors significantly increase impulse buying behavior. These findings suggest that marketers on social commerce platforms like TikTok Shop can enhance impulse purchases by appealing to hedonic motivations, offering price discounts, and catering to various shopping lifestyles. Highlights: 1. Key Drivers: Hedonic motivation, price discounts, and shopping lifestyle drive impulse buying.2. Data Analysis: SPSS 22 analysis of 160 respondents confirms significant variable impact.3. Marketing Insight: Social commerce can boost impulse buys with targeted discounts and motivations. Keywords: Hedonic Shopping, Price Discounts, Shopping Lifestyle, Impulse Buying, TikTok Shop